Convivere con l’alterità. I legami, gli spazi e il lockdown - Marabello, Selenia; Parisi, Maria Luisa (Antropologia Pubblica, 2024)
In exploring a project named Vesta, which aims at giving a temporary ‘home’ to the unaccompanied minors migrants involving committed Italian families, we shed light on the ideas and representations of ‘living together’ by autochthonous and migrants. Yet, considering the current pandemic measures of containment – social distancing and isolation at home – we analysed how the lockdown challenged the cohabitation among young migrants and their recipient’s families. Observing domestic spaces and family ideas we investigated how the lockdown and sickness representations contributed to mould and re-elaborate symbolic and social meanings given to ‘the living together’.